2009
DOI: 10.1007/s12520-009-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological collagen: Why worry about collagen diagenesis?

Abstract: DNA appears to decay by random chain scission resulting in a predictable range of fragment lengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 54 publications
5
95
1
1
Order By: Relevance
“…Even this technique's strongest proponents acknowledge, however, that AAA will also fail to identify all cases of contamination, that serious methodological issues exist with such analysis (Harbeck and Grupe, 2009:55;Hedges and van Klinken, 1992; van Klinken, 1999), and that the amino acid composition of collagen extracts does not vary significantly until collagen is almost entirely degraded (Beeley and Lunt, 1980;Dobberstein et al, 2009;van Klinken, 1999). Furthermore, given the cost of such analysis (US$100e200 per sample), and as van Klinken (1999:690) found specific amino acid assays to be "relatively unhelpful for the assessment of 'collagen' quality," above and beyond those identified by chemical and elemental measures, we chose not to attempt to assess the preservation of these samples by AAA.…”
Section: Methodsmentioning
confidence: 99%
“…Even this technique's strongest proponents acknowledge, however, that AAA will also fail to identify all cases of contamination, that serious methodological issues exist with such analysis (Harbeck and Grupe, 2009:55;Hedges and van Klinken, 1992; van Klinken, 1999), and that the amino acid composition of collagen extracts does not vary significantly until collagen is almost entirely degraded (Beeley and Lunt, 1980;Dobberstein et al, 2009;van Klinken, 1999). Furthermore, given the cost of such analysis (US$100e200 per sample), and as van Klinken (1999:690) found specific amino acid assays to be "relatively unhelpful for the assessment of 'collagen' quality," above and beyond those identified by chemical and elemental measures, we chose not to attempt to assess the preservation of these samples by AAA.…”
Section: Methodsmentioning
confidence: 99%
“…As such, additional controlled studies on the influence of various diagenetic processes (e.g. Dobberstein et al, 2008Dobberstein et al, , 2009Harbeck and Grupe, 2009) on the bones of mammals, fish and birds would be extremely beneficial.…”
Section: Bonementioning
confidence: 99%
“…To date, a number of studies have attempted to define and refine such criteria (Ambrose, 1990;DeNiro, 1985;DeNiro and Weiner, 1988;Dobberstein et al, 2009;Grupe and Turban-Just, 1998;Grupe et al, 2000;Harbeck and Grupe, 2009;Schoeninger et al, 1989;Tuross et al, 1988Tuross et al, , 1989van Klinken, 1999), but all have focused exclusively on mammalian bone. One notable exception is the work of Nehlich and Richards (2009), who suggested that because of differences in the amino acid composition of collagen, the quality criteria for sulfur isotopic analysis (C:S ratio) should be different for fish and mammalian bone.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the rate of these degradation pathways are affected by temperature, as higher burial temperatures have been shown to accelerate these processes (6,8). Though relatively unusual, the first of these three pathways results in a slower deterioration process, which is more generally mitigated under (6) specific environmental constraints, such as geochemical stability (stable temperature and acidity) that promote bone mineral preservation.…”
mentioning
confidence: 99%